2017
DOI: 10.5194/acp-2017-853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Total ozone trends from 1979 to 2016 derived from five merged observational datasets – the emergence into ozone recovery

Abstract: Abstract.We report on updated trends using different merged datasets from satellite and groundbased observations for the time period 1979 until 2016. Trends were determined by application of a multiple linear regression (MLR) to annual mean zonal mean data. Merged datasets used are NASA MOD V8.6 and NOAA MERGE V8.6, both based upon data from the series of SBUV and SBUV-2 satellite instruments (1978-present) and the GTO (GOME-type Total Ozone) and GSG (GOME-SCIAMACHY-5 GOME2) merged datasets (1995-present) th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Two recently published papers (Steinbrecht et al, 2017;Weber et al, 2017) show that total ozone and ozone profile trends are consistent with earlier WMO (2014) findings. Despite the addition of 4 more years since WMO 40 (2014), Weber et al (2017) show that for most datasets and regions the trends in total ozone, since stratospheric halogens reached their maximum around 1997, are not significantly different from zero.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Two recently published papers (Steinbrecht et al, 2017;Weber et al, 2017) show that total ozone and ozone profile trends are consistent with earlier WMO (2014) findings. Despite the addition of 4 more years since WMO 40 (2014), Weber et al (2017) show that for most datasets and regions the trends in total ozone, since stratospheric halogens reached their maximum around 1997, are not significantly different from zero.…”
Section: Introductionsupporting
confidence: 74%
“…Despite the addition of 4 more years since WMO 40 (2014), Weber et al (2017) show that for most datasets and regions the trends in total ozone, since stratospheric halogens reached their maximum around 1997, are not significantly different from zero. In the case of ozone profile trends, however, Steinbrecht et al (2017) confirmed increasing trends in the upper stratosphere (2 hPa) as first reported in WMO (2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note here that the SBUV total column ozone non-linear trend initially increases from 1998 and then peaks around 2011, before decreasing. Frith et al (2014) and Weber et al (2017) found similar behaviour when applying linear trend fits to SBUV total column ozone, fixing the start date in January 2000 and incrementally increasing the end date, i.e. the largest positive trend was found for the period 2000-2011 and thereafter trends decreased.…”
Section: Stratospheric and Total Column Ozone Post-1997 Changesmentioning
confidence: 71%
“…However, non-polar (< 60 • ) total column ozone levels have remained stable since 2000 (WMO, 2014), with most latitudes displaying a positive, but non-significant, decadal trend (WMO, 2014). Results from Frith et al (2014) and Weber et al (2017) suggest a potential peak in positive trends around 2011, after which positive trends decreased, and while uncertainties shrink, significance remains elusive.…”
Section: Introductionmentioning
confidence: 99%